Aerobic denitrification performance of strain Acinetobacter johnsonii WGX-9 using different natural organic matter as carbon source: Effect of molecular weight. (1st November 2019) - Wen, Gang; Wang, Tong; Li, Kai; Wang, Hanyue; Wang, Jingyi; Huang, Tinglin
Abstract: The aim of this study was to investigate the effect of natural organic matter (NOM) including humic acid (HA) and fulvic acid (FA), intracellular organic matter (IOM) extracted from Microcystis aeruginosa (MA) and Chlorella sp. (CH), and their different molecular weight (MW) fractions on the aerobic denitrification performance of bacterial strain WGX-9 by monitoring nitrogen removal efficiency and testing changes in organic matter with HA, FA, MA-IOM and CH-IOM as the sole carbon source. Strain WGX-9 was identified as Acinetobacter johnsonii and exhibited excellent aerobic denitrification capability. The nitrate removal efficiency with IOM as the sole carbon source was relatively higher than that with NOM as the sole carbon source. The prepared NOM and extracted IOM samples were separated into six fractions with MW cut-offs of 100, 30, 10, 5 and 1 kDa. The fraction of MW > 100 kDa contributed the largest amount to the MW distribution, accounting for 77.11%, 29.00%, 44.97% and 24.81% of HA, FA, MA-IOM, and CH-IOM, respectively. Nitrate removal efficiency was improved with decreasing MW of organic matter. For example, nitrate removal efficiency was 26.50%, 32.41%, 27.88% and 43.89% using HA, FA, MA-IOM, and CH-IOM fractions of MW > 100 kDa as the carbon source, whereas with MW < 1 kDa, it increased to 36.67%, 37.88%, 60.90%, and 68.90%, respectively. This is probably because the smaller MW fraction is more suitable for bacterial growth. These results demonstrate that the strain WGX-9 can utilize lower MW organic matter, which lays the foundations for nitrogen removal in actual drinking water reservoirs. Graphical abstract: Image 1 Highlights: Acinetobacter johnsonii WGX-9 has excellent aerobic denitrification performance. IOM as carbon source show higher nitrate removal relative to NOM, but lower than sodium acetate. The nitrate removal efficiency was improved with the MW of organic matter decrease. The tyrosine/tryptophan-like organic matter are preferentially used by microorganisms.